THE EFFECTIVENESS OF BILINGUAL PROGRAM AT SCHOOL - Evi Nopiyanti (Deiksis, 2013)
This article talks about bilingualism applied in Indonesia. In this modern era, education program has been developed to fulfill the society’s need. For instance, English takes a part to make everyone all over the world have prestige degree in almost each of life aspects. School as an assimilation culture place, whereas culture is mixed together so that it enriches more knowledge and information, that makes language more being developed. That Children need process to achieve language acqusition. Meanwhile, principles and teachers are always keeping to explore the goal, weakness, strength and startegic to maintain the reason about effectiveness of bilingual program.Key words: The effectiveness, bilingual program,school